S50 Hypersensitivity pneumonitis complicated by pulmonary hypertension; patient characteristics and response to targeted therapy. (14th November 2013) - Garfield, BE; Keir, GJ; Price, LC; Wells, AU; Renzoni, E; Maher, TM; Marino, P; Dimopoulos, K; Wort, SJ
Abstract : Background: Hypersensitivity pneumonitis (HP) results from repeated exposure to a sensitizing antigen, normally an organic particle. It can be acute, sub-acute or chronic (1). There is very little literature describing the association of pulmonary hypertension (PH) with HP (2). We aimed to summarize the clinical characteristics and outcomes including responses to targeted therapy in patients with HP and PH in a tertiary referral centre. Methods: Cases diagnosed between 1992 and 2008 were identified through a central database. PH was defined as mean pulmonary artery pressure ≥25mmHg on right heart catheter or right ventricular systolic pressure of ≥50 mmHg on echocardiogram. Data was collected through case note and electronic record review. Analysis was performed using Graphpad prism. Results: Nineteen consecutive patients with PH and HP were identified. Fifteen had chronic HP as evidenced by fibrosis on HRCT, whilst 4 had sub-acute disease. Demographic and baseline findings are listed in table 1 . Right ventricular (RV) dysfunction was found in 14 patients. Ten were treated with targeted therapy (sildenafil +/- endothelin receptor antagonist), of these 7 had evidence of RV dysfunction. Median BNP fell between pre and first post sildenafil measurement from 80 to 27 pmol/L but failed to reach statistical significance (p = 0.11). RV function improved in 2 of 6 patients with available follow up echocardiogram at a median of 4 months. There was no consistent change in RVSP, TR velocity or pulmonary acceleration time with treatment. Twelve patients died, a median of 8 months (0.2 - 46) from diagnosis of PH. Although not reaching statistical significance, the median arterial pO2 was higher in survivors (7.25 versus 5.85 kPa: p = 0.11). Conclusion: Chronic and sub-acute HP can be complicated by PH. Mortality in this group was extremely high despite targeted therapy. PO2 was generally lower in those who died. The diagnosis of PH in HP patients may well be a pre-terminal event. Further work is needed to understand which patients may respond to advanced therapies. References: A Wells and N Hirani (2008) Interstitial Lung Disease Guidelines. Thorax . 63v1–v58 D S Koschel et al. (2012) Lung . 190(3):295–302